solve the given pair of linear equation
![(a - b)x + (a + b)y = a ^{2} - 2ab - b ^{2} \\ (a + b)(x + y) = a ^{2} + b ^{2} (a - b)x + (a + b)y = a ^{2} - 2ab - b ^{2} \\ (a + b)(x + y) = a ^{2} + b ^{2}](https://tex.z-dn.net/?f=%28a+-+b%29x+%2B+%28a+%2B+b%29y+%3D+a+%5E%7B2%7D++-+2ab+-+b++%5E%7B2%7D++%5C%5C+%28a+%2B+b%29%28x+%2B+y%29+%3D+a+%5E%7B2%7D++%2B+b+%5E%7B2%7D+)
Answers
=> (a-b) x + (a + b) y = a² - 2ab - b²…………(1)
=> (a + b) (x + y) = a² + b²……………………(2)
=> Equation (2) can be written as (a + b)x+ => (a+b) y = a² + b²………….(3)
=> Now we have to solve equation (1) and (3)
=> (a-b) x + (a + b) y = a² - 2ab - b²,…………(1)
=> (a + b)x+ (a+b) y = a² + b²………….(3)
=> Subtracting equation (3) from (1) we get
=> (a-b-a-b) x = a² - 2ab - b²- a² - b²
=> -2b x = - 2ab -2 b²
=> -2b x =-2b(a+b)
=> dividing both sides by -2b
= x = a+b
=> Now substitude x=a+b in equation (1) we get
=> (a-b)(a+b) + (a + b) y = a² - 2ab - b²
=> a² - b² + + (a + b) y = a² - 2ab - b²
=> Subtracting a² - b² from both the sides
=> (a + b) y = a² - 2ab - b² - a² + b²
=> (a + b) y = - 2ab
=> y = - 2ab /(a+b)
=>Answer x = a+b , y = - 2ab /(a+b)
I hope this will help you dear..
Always stay safe and stay healthy..
hope it helps you
be brainly
![](https://hi-static.z-dn.net/files/d0f/21c0996372ef3f86db4c3231fc3f1b13.jpg)